1993
DOI: 10.1161/01.str.24.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a hypothermic pharmacological agent in gerbil forebrain ischemia.

Abstract: Background and Purpose: The novel muscarinic cholinergic partial agonist U-80816E was tested in the gerbil brief bilateral carotid occlusion ischemia model based on the rationale that the compound's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 32 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Histological outcomc was assessed at 4 and 21 days after ischemia. Uccause hyporhermia from physical or pharmacological intervention is an effective cerebral tieuroprotectant (Busto ct al., 1987;Welsh et al, 1990: Dietrich et al, 1993Hall et al, 1993;Colbourne and Corbett, 1994), we also assessed the role of hypothermia in tiagabine-mediated protection. These results have been presented previously in a preliminary form (Inglcfield et al, 1994).…”
mentioning
confidence: 99%
“…Histological outcomc was assessed at 4 and 21 days after ischemia. Uccause hyporhermia from physical or pharmacological intervention is an effective cerebral tieuroprotectant (Busto ct al., 1987;Welsh et al, 1990: Dietrich et al, 1993Hall et al, 1993;Colbourne and Corbett, 1994), we also assessed the role of hypothermia in tiagabine-mediated protection. These results have been presented previously in a preliminary form (Inglcfield et al, 1994).…”
mentioning
confidence: 99%
“…However, other more selective central nervous system cholinergic agonists can produce hypothermia with reduced peripheral effects. 3 A recent article 4 has shown that such drugs, when administered before induction of temporary forebrain ischemia and during reperfusion in a gerbil model, produce reduction in the amount of neuronal loss by their hypothermic effect. The temperature reduction of approximately 2°C produced in these experiments would be expected to have profound cerebral protective effects.…”
Section: Pharmacologically Induced Hypothermia For Cerebral Protectiomentioning
confidence: 99%
“…These are, of course, measurements of spatial peak-temporal average (SPTA) made in water, and the maximum value is reduced to 240 mW/cm 2 by the application of the Food and Drug Administration's formula originally used for estimating in situ intensity for fetal insonation 4 and to 51 mW/cm 2 by using the unit of estimated intracranial intensity (EII) proposed by me as being more realistic for TCD applications. .…”
Section: Effect Of Emitted Power On Waveform Intensity In Transcraniamentioning
confidence: 99%
“…Several candidates targeting distinct signaling pathways have been tested for PIH including a neurotensin receptor agonist HPI201/ABS201 in stroke and TBI models [3, 4], a cannabinoid receptor agonist WIN55, 212-2 in a ventricular defibrillation CA model [5], the A1 adenosine receptor agonist 8-SPT in an asphyxial-CA model [6], the muscarinic cholinergic partial agonist U-80816E in the gerbil brief bilateral carotid occlusion ischemia model [7], a dopaminergic agonist Talipexole in stroke model [8], a serotonergic agonist S14671 in a stroke model [9] and the transient receptor potential cation channel vanilloid type 1 (TRPV1) agonist dihydrocapsaicin (DHC) in a stroke model [10]. …”
Section: Introductionmentioning
confidence: 99%